Normative data and objective benchmarks for selected force plate tests for professional and youth soccer players in the English Football League - Badby, A. J.; Comfort, P.; Ripley, N. J.; Mundy, P. D.; Soriano, M. A.; Robles-Palazón, F. J.; Fahey, J.; Sindall, P.; Bramah, C.; McMahon, J. J. (Journal of Sports Sciences, 2025)
The aim of this study was to establish objective benchmarks for countermovement jump (CMJ), countermovement rebound jump (CMRJ), and isometric mid-thigh pull (IMTP) metrics in male professional and youth soccer players. Professional (N = 139; age: 24 ± 5 years; height: 184 ± 7 cm; mass: 81 ± 9 kg) and youth (N = 137; age: 17 ± 1 years; height: 178 ± 17 cm; mass: 72 ± 8 kg) soccer players were recruited from 7 separate clubs. Many CMJ (25/32), CMRJ (24/30), and (2/2) IMTP metrics discriminated between age groups. Significant (p < 0.05) differences were identified in CMJ outcome (4/4), propulsive kinetic (6/6), and relative propulsive kinetic (4/4) metrics, but trivial non-significant (p > 0.05) differences were identified in strategy (4/4) metrics. Rebound jump portion propulsive kinetic (4/4) metrics and braking depth demonstrated moderate to large differences between groups, but only one relative propulsive kinetic (1/4) metric demonstrated significant (p < 0.01) differences. Professional soccer players also demonstrated significantly (p < 0.001) greater IMTP peak force (3031 ± 549 N vs 2441 ± 452 N; g = 0.788) and relative peak force (37.39 ± 5.35 N/kg vs 34.01 ± 4.74 N/kg; g = 0.446) than youth soccer players.